Physical exercises to face the exceptional situations in older adults with physical motor limitations at the Marialina community. Santiago de Cuba - Zulinma Martínez-Nariño; Luis Orlando Caballero-Riera; Emilio Oberto-Dinza (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2015)
The objective of the given research reflection is to include to the disable people programm, an action system addressed to the elderly people incorporation with physical-motor disabilities into the physical exercises. It is considered as the main theoretic reference, the model of therapeutic physical culture generalities and rehabilitation as the essential support to develop physical activity as a therapeutic way suggested by the authors Dr. C. Armado Semanat Belisón, and M. Sc. Francisco Horsford Hernández.